Financial development and shadow economy in Africa: evidence from panel quantile regression (2023)
"The study investigated the impact of financial development on shadow economy in Africa, using data for 41 African countries. The informal outputs, computed by Elgin et al. (2021), and the three financial development indicators were sourced from the World Bank and International Monetary Fund (IMF) respectively. The dynamic panel quantile regression technique was employed as it captures better the nature of the African economy and the heterogeneous nature of the shadow economies. The study shows that average FIA and FID in Africa is 0.074 and 0.160 respectively; suggesting that accessing credit from financial institution, as well as the coverage of credit and other financial services in Africa is low and could be accompanied with high degree of bottlenecks. The FIE on average is 0.520; suggesting that credits from financial institution in Africa are used for their intended purposes. However, financial development must be pursued alongside other macroeconomic goals, particularly urbanization.